GROWTH AND YIELD OF RED LETTUCE (Lactuca sativa L.) IN VARIOUS TYPES COMBINATION OF LIQUID FERTILIZER FLOATING HYDROPONIC SYSTEM - Zakka Hammad Ghifari; Sumarwoto Sumarwoto; Suwardi Suwardi (UNIVERSITAS PEMBANGUNAN NASIONAL ”VETERAN” YOGYAKARTA, 2021)
Lettuce (Lactuca sativa L.) is one of the selected seasonal crops which is cultivated with a hydroponic system. In general, hydroponics uses water with chemical nutrition, AB Mix 800 ppm. One way to reduce the negative impact of chemicals on health is the use of Liquid Organic Fertilizers (LOF). The purpose of this research is to search for the combination of Liquid Organic Fertilizer (LOF) as hydroponic nutrition which can produce the best lettuce plant growth, thereby minimizing the use of chemicals. The research method used is CRD (completely randomized design) with two stages of research. The first stage of the research consisted of six treatments that are Liquid Organic Fertilizer (LOF) of rabbit urine, Azolla extract, goat urine, cow urine, vegetable waste, each treatment contains 10% concentration and AB Mix 800 ppm as control with 5 repetitions. The results of the first stage of research are taken from the top two as the basis for the second stage of research that is rabbit urine and Azolla extract. The second stage of the research consisted of ten treatments that are 100% LOF of Azolla extract, 100% LOF of rabbit urine, 100% AB Mix 800 ppm, 50% Azolla extract + 50% rabbit urine, 50% Azolla extract + 50% AB Mix 800 ppm, 50% rabbit urine + 50% AB Mix 800 ppm, 75% Azolla extract + 25% rabbit urine, 75% rabbit urine + 25% Azolla extract, 75% Azolla extract + 25% AB Mix 800 ppm ,75% rabbit urine + 25% AB Mix 800 ppm with 3 repetition. The data obtained are analyzed using Analysis of Variance (ANOVA) at the test level of 5%, then further tested using Duncan’s Multiple Range Test (DMRT) with the level of 5%. The best results of the first research are Liquid Organic Fertilizer (LOF)of Azolla extract and rabbit urine. The best results of the second research obtained from the treatment of 50% Azolla extract + 50% AB Mix 800 ppm and 75% Azolla extract and 25% AB Mix 800 ppm. It proofed with the high result in treatment of fresh weight of the plant.